Сучасний стан процедури отримання замовником будівництва дозвільних документів - Титок, В. В.; Євдоченко, О. М. (Ways to Improve Construction Efficiency, 2012)
In the article proposed the algorithm for obtaining the customer permission for construction works. Consider the current state of the licensing system in Ukraine.